2022
DOI: 10.1245/s10434-022-11506-3
|View full text |Cite
|
Sign up to set email alerts
|

Global Forum of Cancer Surgeons: Cancer Surgery During the COVID-19 Pandemic: Impact and Lessons Learned

Abstract: Background. The purpose of this article is to summarize the opinions of the surgical oncology leaders from the Global Forum of Cancer Surgeons (GFCS) about the global impact of COVID-19 pandemic on cancer surgery. Methods. A panel session (virtual) was held at the annual Society of Surgical Oncology 2021 International Conference on Surgical Cancer Care to address the impact of COVID-19 on cancer surgery globally. Following the virtual meeting, a questionnaire was sent to all the leaders to gather additional op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In our study, the COVID‐19 pandemic and the lack of availability of hospital beds 15–20 in a way “forced” all the providers to changed clinical practice and implement ERAS protocols. The outpatient mastectomy rate at our institution tripled during COVID‐19 from 17% to 51%.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, the COVID‐19 pandemic and the lack of availability of hospital beds 15–20 in a way “forced” all the providers to changed clinical practice and implement ERAS protocols. The outpatient mastectomy rate at our institution tripled during COVID‐19 from 17% to 51%.…”
Section: Discussionmentioning
confidence: 95%
“…Delays in diagnosis and treatment can reduce overall survival 24 , 25 and this was the case during the COVID-19 pandemic, when most healthcare resources were reallocated to treat COVID-19 patients 10 , 26 . Few studies have reported the management of patients with primary liver cancer during the COVID-19 pandemic, and these have mainly focused on the diagnosis of primary liver cancer rather than the outcomes in these patients 2 , 3 , 7 , 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The SARS-CoV-2 outbreak started in December 2019 in China and was declared a global pandemic by the World Health Organization (WHO) in March 2020 1 . Since then, approximately 250 million people have been infected with SARS-CoV-2 and up to 5 million have died of COVID-19, the disease caused by the virus 2 . The pandemic has placed a grave burden on everyday life around the world 3 , including healthcare services 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Working together with our international partners, there have been several position papers highlighting the issues of cancer care internationally including a position statement to promote cancer care globally published in 2020 in Annals of Surgical Oncology , 8 and a paper on the impact of COVID-19 on cancer surgery practices worldwide has been published this year in Annals of Surgical Oncology . 9 Programs like this can help increase our visibility on the international front.…”
mentioning
confidence: 99%